Financial Ratio Analysis and Health Level of PT Wijaya Karya (Persero) Tbk Based on Altman Z-Score - Eka Putri, Annisa Anindya; Resha Maielyana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study employs a quantitative descriptive approach to evaluate the financial performance and health of PT Wijaya Karya (Persero) Tbk. It involves analyzing the company's financial ratios, including profitability, liquidity, activity, and solvency ratios, using the financial statements available on the IDX website from 2020-2023. The company's health is assessed using the four-variable version of the Altman Z-Score method. The results indicate a declining trend in liquidity ratios, suggesting a reduced ability to meet short-term obligations. Fluctuations in solvency ratios imply increased risk or development through higher borrowing. Activity ratios reflect an overall increase, but with fluctuations in fixed asset utilization and collection efficiency. Profitability ratios demonstrate a downward trend over time. According to the Altman Z-Score analysis, the company faces a high risk of bankruptcy due to its vulnerable health level, necessitating immediate action to address this critical issue.